সোনালি আশা: Bangabandhu Jute and Textile Museum, Tarabo, Rupganj, Narayanganj - Onty, Esrat Jahan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.